The effect of alcohol consumption and contextual cues on the evaluation of new brands of alcoholic beverages at the POS. (July 2020) - Khandeparkar, Kapil; Motiani, Manoj
Abstract: As per ELM, consumers' motivation and ability influence the route through which they process new information. A higher magnitude of these two factors leads to systematic information processing whereas a lower level leads to peripheral information processing. This research manipulated consumers' motivation by varying the contextual cues like bundle partner's brand image and functional relationship between the items whereas their ability was manipulated by alcohol administration to test its impact on the quality perception of a new brand of alcoholic beverage and the purchase intention of the bundle. A lower magnitude of motivation and ability increases the chances of adopting a categorisation approach to evaluate the new brand, and subsequently, the entire bundle. Therefore, a bundle's contextual cues dictate the evaluation of the new brand. Additionally, the alcohol priming effect leads to a greater propensity to try new brands of alcoholic beverages even if their quality is perceived to be inferior.